MARIOLOGI KONSILI VATIKAN II: Mikrohistori Mariologi Pra-Konsili dan Magna ChartaMariologi Post-Konsili - Gregorius Pasi (Litbang STFT Widya Sasana Malang, 2016)
The teaching of the Second Vatican Council on Mary (the mother of Jesus) is laid down in Chapter VIII of the Dogmatic Constitution on the Church, Lumen Gentium (LG). Lumen Gentium’s chapter VIII represents a 20th century microhistory of mariology and a magna charta of post-conciliar mariology. The purpose of this essay is exposing three matters. Firstly, showing evidence that the elaboration of the marian texts of Vatican II is a reproduction of pre-conciliar mariological struggles. Secondly, articulating the character of Vatican II’s mariology as a fundament for post-conciliar mariology. Thirdly, pointing at some matters somewhat neglected by Vatican II’s mariology and offering it as “home work” for post-conciliar mariology. In this framework, this essay will not analyze the content of Lumen Gentium’s mariology article by article, but evaluate it comprehensively. May this essay provide a kind of orientation to the reader in having an idea of post-conciliar mariology